2005
DOI: 10.1128/cdli.12.7.845-847.2005
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G Subclass Profile of Antimeasles Response in Vaccinated Children and in Adults with Measles History

Abstract: The aim of this study was to investigate measles-specific immunoglobulin G (IgG) subclass profile in vaccinated children and in adults with natural infection. Serum samples were collected before and 30 days after vaccination. The sera from 51 late convalescent adults and seven adults with natural measles infection at the 12th day after onset of rash have been also investigated. Measles IgG antibodies and specific IgG subclasses were tested by enzyme-linked immunosorbent techniques. In children younger than 3 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…IgG1 was expected, as the subclass is commonly induced after viral infections such as measles, hepatitis B, human T-lymphotropic virus, rubella, and B19V, which like AAV is a member of the Parvoviridae (Morgan-Capner and Thomas, 1988;Lal et al, 1993;Franssila et al, 1996;Rey et al, 2000;Toptygina et al, 2005). IgG2 was also shown to be a constituent of the AAV-specific antibody response (Madsen et al, 2009;Murphy et al, 2009), but it is low as for B19V (Lal et al, 1993;Franssila et al, 1996;Toptygina et al, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…IgG1 was expected, as the subclass is commonly induced after viral infections such as measles, hepatitis B, human T-lymphotropic virus, rubella, and B19V, which like AAV is a member of the Parvoviridae (Morgan-Capner and Thomas, 1988;Lal et al, 1993;Franssila et al, 1996;Rey et al, 2000;Toptygina et al, 2005). IgG2 was also shown to be a constituent of the AAV-specific antibody response (Madsen et al, 2009;Murphy et al, 2009), but it is low as for B19V (Lal et al, 1993;Franssila et al, 1996;Toptygina et al, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…Although increased levels of Th2 cytokines such as IL-4 and IL-10 were not observed in response to measles vaccination in infants [11], IFN-g responses may be insufficient to induce a complete deployment of the Th1 response. The isotypes of MV-specific antibodies have been previously studied after immunization and natural infection [32][33][34][35][36]. These studies show that, in general, IgG3 is detected early and associated with decreasing levels over time, whereas levels of IgG1 continue to increase; IgG2 is rarely observed.…”
Section: Discussionmentioning
confidence: 95%
“…As circulating antibody titers are known to vary over time based on the immunological state of the individual (Toptygina et al, 2005), the maternal antibody profile observed at the time of the registration of her child into the CHARGE study may be slightly different than during gestation. However, it has been demonstrated that antibodies, such as those generated in response to vaccination, can persist for many years due to the maintenance and subsequent polyclonal reactivation of memory B cells (Shinefield et al, 2002).…”
Section: Discussionmentioning
confidence: 99%